2020
DOI: 10.6061/clinics/2020/e1450
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neutrophil-to-Lymphocyte Ratio and Systemic Lupus Erythematosus: A Meta-analysis

Abstract: Systemic lupus erythematosus (SLE) is a chronic systematic autoimmune disease. Current methods of diagnosing SLE or evaluating its activity are complex and expensive. Numerous studies have suggested that neutrophil-tolymphocyte ratio (NLR) is closely correlated with the presence of SLE and its activity, suggesting that it may serve as a diagnostic and monitoring indicator for SLE. Therefore, we performed a meta-analysis to systematically assess the association between NLR and SLE. We performed a literature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
0
22
0
2
Order By: Relevance
“…Fourteen studies with 1246 SLE patients (Ma et al) and 1781 SLE patients (Wang et al) were included in this meta-analysis. The meta-analysis demonstrated elevated levels of NLR and PLR in patients with active SLE (Ma et al) and positive clinical value of NRL for diagnosing SLE, active SLE or LN (Wang et al) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies with 1246 SLE patients (Ma et al) and 1781 SLE patients (Wang et al) were included in this meta-analysis. The meta-analysis demonstrated elevated levels of NLR and PLR in patients with active SLE (Ma et al) and positive clinical value of NRL for diagnosing SLE, active SLE or LN (Wang et al) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic inflammatory response was investigated by the neutrophil and lymphocytes counts and by the neutrophil/lymphocyte ratio, as described in other autoimmune diseases [ 22 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that NLR was a useful marker to assess disease activity both in jSLE and aSLE patients (11,(20)(21)(22). A meta-analysis demonstrated that NLR had positive clinical value for diagnosing SLE, active SLE, and LN (11,24). Ayna et al reported a NLR cut-off value of 1.93 to differentiate SLE patients with or without nephritis (25).…”
Section: Discussionmentioning
confidence: 99%